Developing a new rock classification based on the abrasiveness, hardness, and toughness of rocks and PA for the prediction of hard dimension stone sawability in quarrying. Issue 6 (2nd November 2017) - Almasi, S. Najmedin; Bagherpour, Raheb; Mikaeil, Reza; Ozcelik, Yilmaz
Abstract: Predicting the sawability of dimension stone is one of the most important factors in the optimized design and cost estimation of quarrying. This paper aims to predict the cutting rate of diamond wire saw (DWS) as main performance criteria. For this purpose, a classification system for ranking the sawability of hard dimension stone based on the toughness, abrasiveness, and hardness of rock was initially developed, and a Hard Dimension Stone Sawability index (HDSSi) was defined. Then, by means of multiple curvilinear regression analysis, the data were analyzed and the relationship between the cutting rate with the HDSSi, and pullback amperage was obtained with a high correlation coefficient (.846) in data training, and .801 in data test. Validation of the model was carried out by considering the t -test, F -test, and the coefficient of determination. During this research, varieties of 11 types of hard rock were cut in a laboratory using a DWS and a fully instrumented cutting platform at different pullbacks. The results show that the cutting rate of hard dimension stones with a DWS can be successfully predicted using the developed model.